2009
DOI: 10.1161/circulationaha.109.872663
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Fibrillin-1 Function Promotes Features of Plaque Instability in Apolipoprotein E–Deficient Mice

Abstract: Background— Arterial stiffness has been associated with an increased cardiovascular risk. The aim of this study was to investigate the interaction between arterial stiffness and atherosclerosis. Methods and Results— Mice with a mutation (C1039G +/− ) in the fibrillin-1 gene leading to fragmentation of the elastic fibers were crossbred with apolipoprotein E–deficient (ApoE −/− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 45 publications
5
78
0
Order By: Relevance
“…1B of Van Herck et al (42)]. In addition, their results showed a significant correlation between increase of arterial wall stiffness in atherosclerotic mice and plaque development.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…1B of Van Herck et al (42)]. In addition, their results showed a significant correlation between increase of arterial wall stiffness in atherosclerotic mice and plaque development.…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, the animal study performed by Van Herck et al (42) showed that an increase of arterial stiffness promotes plaque development. In their study, the effect of increased arterial stiffness on atherosclerosis was investigated by feeding a Western-type diet for 10 or 20 wk apolipoprotein E (ApoE)-deficient (ApoE Ϫ/Ϫ ) and ApoE Ϫ/Ϫ C1039G Ϫ/Ϫ mice with mutation in the fibrillin-1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, apolipoprotein E deficient mice (ApoE À/À ) with a heterozygous mutation in the fibrillin-1 gene (Fbn1 C1039Gþ/À ) were used. Recently, we reported that this unique mouse model shows an accelerated plaque progression, spontaneous plaque ruptures, myocardial infarction and sudden death [32,33]. Therefore, it is an adequate model to study the effects of mental stress on plaque vulnerability and the occurrence of myocardial infarctions.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, most relevant data on IPH comes from clinical studies and analysis of human tissues. Nevertheless, a model resulting from a cross between apoE KO and fibrillin KI (Marfan) mice has been reported to develop important intraplaque neo-angiogenesis with the presence of IPH [15,16].…”
Section: Introduction: Phylogeny Of the Arterial System And Teleonomimentioning
confidence: 99%